2018
DOI: 10.1080/14756366.2018.1463221
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial activity of sulphonamide nanoemulsions targeting theβ-carbonic anhydrase fromLeishmaniaspecies

Abstract: The β-carbonic anhydrase (CA, EC 4.2.1.1) from Leishmania spp. (LdcCA) is effectively inhibited by aromatic/heterocyclic sulphonamides, in the low nanomolar range, but no in vitro antileishmanial activity was detected for such compounds. We formulated some of these sulphonamides as nanoemulsions (NEs) in clove oil, and tested them in vitro against Leishmania infantum MHOM/BR/1974/PP75 and Leishmania amazonensis IFLA/BR/1967/PH8 strains. Interesting inhibitory concentrations IC50 were observed for some of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Inhibitors such as chalcones that block the activity of these trypanosomatid enzymes may be effective in treatment of leishmaniasis [29]. β-carbonic anhydrase [30], acid phosphatases [31], uracil DNA glycosylase [32] and Type 2 NADH dehydrogenase [33] are other potential therapeutic targets that are being explored. NLR (NOD-Like Receptor) family member NOD2 has also been implicated as an essential therapeutic target [34].…”
Section: Therapeutic Targets and Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitors such as chalcones that block the activity of these trypanosomatid enzymes may be effective in treatment of leishmaniasis [29]. β-carbonic anhydrase [30], acid phosphatases [31], uracil DNA glycosylase [32] and Type 2 NADH dehydrogenase [33] are other potential therapeutic targets that are being explored. NLR (NOD-Like Receptor) family member NOD2 has also been implicated as an essential therapeutic target [34].…”
Section: Therapeutic Targets and Inhibitorsmentioning
confidence: 99%
“…Recently, antileishmanial activity of sulphonamide nanoemulsions have been reported that target the leishmanial β-carbonic anhydrase [30]. Linalool-loaded gold nanoparticles have also been found to exhibit therapeutic effectiveness against Leishmania [49].…”
Section: Nanomedicinesmentioning
confidence: 99%
“…The physiological relevance of β-CAs in many organisms, including protozoans belonging to the Amoebozoas, is yet to be discovered. However, in Leishmania spp., a β-class CA enzyme (LdcCA) was recently shown to be a potential drug target [19,20,21]. Indeed, the inhibition of protozoan β-CAs with sulfonamides, formulated as nanoemulsions, had a profound effect on the survival and growth of L. amazonensis and L. infantum , two species which provoke serious disease in the tropical and subtropical countries [21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that the inhibition of the α- or β-CAs from the pathogenic protozoans Trypanosoma cruzi [28] or Leishmania spp. [29] has a potent anti-protozoan effect, with the possibility to inhibit the growth of the pathogen. Considering that the genome of E. histolytica has been published [30], we decided to investigate in detail whether the β-CA present in this pathogenic protozoan may have a similar role to the enzymes investigated earlier in other pathogenic protozoans [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…[29] has a potent anti-protozoan effect, with the possibility to inhibit the growth of the pathogen. Considering that the genome of E. histolytica has been published [30], we decided to investigate in detail whether the β-CA present in this pathogenic protozoan may have a similar role to the enzymes investigated earlier in other pathogenic protozoans [28,29]. Here we report an investigation of the catalytic activity and the sulfonamide/sulfamate inhibition profile of the recombinant enzyme belonging to the β-class, identified in the genome of the pathogenic protozoan E. histolytica , denominated EhiCA.…”
Section: Introductionmentioning
confidence: 99%